The Knowledge and Attitudes of Medical Students, Nurse Trainees, and Pediatric Patients’ Caregivers About Influenza and Influenza Vaccination in Prepandemic Era - Soner Sertan Kara; Seher Bacak; Alper Aslan; Şükrü Güngör (Trends in Pediatrics)
Objective: Influenza is a highly contagious respiratory infection influencing all aged people. Healthcare workers (HCWs) not only are vulnerable to influenza infection, but also act as a possible mediator for infection transmission. The best way to prevent influenza is annual vaccination. The aim of this study is to evaluate the knowledge and attitudes of medical students, nurse trainees, and pediatric patients’ caregivers about influenza and influenza vaccination in our tertiary hospital.